Cerros, nevados y páramos: un intento de arqueología etnográfica - Bernand, Carmen (Revista Española de Antropología Americana, 2008)
Considering a cross perspective among archaeology, ethnohistory and ethnography, this paper aspire to rebuilding the relationship between prehispanic cultures and the cosmos, specially from the sacrality of mountains and huacas. Thus, revisiting their own fieldworks in the Ecuadorian sierra, the author try to revitalizing the importance of historical contexts in the perception of this cosmic relations, tracking the ideological continuities which speak about the mountains as dangerous spaces where different forms of alterity live.